2001
DOI: 10.3109/10929080109146002
|View full text |Cite
|
Sign up to set email alerts
|

Fixation-Based Surgery: A New Technique for Distal Radius Osteotomy

Abstract: Both studies showed that the computer system is simple to use. The planning system allowed the surgeon to perform multiple simulations of the surgical procedure preoperatively, which were used to optimize the plan and identify potential problems during realignment. The use of a fixation-based technique avoided the complexity of attempting to guide the surgeon to realign a bone fragment in six degrees of freedom of correction, and eliminated the use of X-ray fluoroscopy for achieving the alignment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…The accuracy and reproducibility of the surgical method with our patient-specific cutting guide and angled jig is superior to other experimental studies that used 3-D navigation-based correction osteotomy methods, such as reported by Croitoru et al [5] ( φ err  ≤ 4.0°; SD ≤ 6.5°) and a more recent study by Westphal et al [22] who showed an overall residual rotation deviation of 4.50° using an expensive robotic-assisted bone fracture reduction method. A limited number of clinical studies that used computer-assisted 3-D planning for correction osteotomy have reported accuracy and reproducibility data.…”
Section: Discussionmentioning
confidence: 62%
“…The accuracy and reproducibility of the surgical method with our patient-specific cutting guide and angled jig is superior to other experimental studies that used 3-D navigation-based correction osteotomy methods, such as reported by Croitoru et al [5] ( φ err  ≤ 4.0°; SD ≤ 6.5°) and a more recent study by Westphal et al [22] who showed an overall residual rotation deviation of 4.50° using an expensive robotic-assisted bone fracture reduction method. A limited number of clinical studies that used computer-assisted 3-D planning for correction osteotomy have reported accuracy and reproducibility data.…”
Section: Discussionmentioning
confidence: 62%
“…All participants suffered from a symptomatic, malunited fracture of the distal radius. For 25 participants, the initial fracture type was not specified [16, 23, 28, 30]; the remaining fractures were extra-articular ( n  = 28) or combined extra- and intra-articular ( n  = 15) in nature. Initial treatment comprised plaster cast immobilization with or without closed reduction in 34 patients and open reduction and internal fixation in 7 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Initial treatment comprised plaster cast immobilization with or without closed reduction in 34 patients and open reduction and internal fixation in 7 patients. Four studies did not report the initial treatment ( n  = 27) [16, 22, 23, 28]. The mean time between injury and the corrective osteotomy was specified for 38 patients and was 30 months (SD 80, range 2–360).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations